2020
DOI: 10.1186/s10020-020-00194-y
|View full text |Cite
|
Sign up to set email alerts
|

circCELSR1 facilitates ovarian cancer proliferation and metastasis by sponging miR-598 to activate BRD4 signals

Abstract: Background: Ovarian cancer is one of the most common gynecologic cancers and has high mortality rate due to the lack of early diagnosis method and efficient therapeutic agents. circCELSR1 is up-regulated in ovarian cancer, but its role and mechanisms in ovarian cancer are unclear. Methods: Gene expression of circCELSR1, miR-598 and BRD4 in ovarian cells was examined by qRT-PCR. Protein level was determined by Western blotting. Bioinformatic analysis and luciferase assay determined the molecular binding among c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Previous study confirmed that BRD4, whose effect was found up-regulated in PA, could regulate the growth of PA tumor in mice [ 30 , 31 ], and therefore, we chose BRD4 for further analysis in the current study. BRD4 has been widely reported to be involved in the development of various cancer types, including multiple myeloma [ 32 ], small cell lung cancer [ 33 ], and ovrican cancer [ 34 ]. The expression of BRD4 could notably affect multiple biological characteristics via different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study confirmed that BRD4, whose effect was found up-regulated in PA, could regulate the growth of PA tumor in mice [ 30 , 31 ], and therefore, we chose BRD4 for further analysis in the current study. BRD4 has been widely reported to be involved in the development of various cancer types, including multiple myeloma [ 32 ], small cell lung cancer [ 33 ], and ovrican cancer [ 34 ]. The expression of BRD4 could notably affect multiple biological characteristics via different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that one of the mechanisms of circRNA is to act as a sponge of microRNA (miRNA) to mediate downstream targeted mRNA expression. 15 In many studies, miR-598 has been identified as a tumor suppressor mediating the regulation of cancer progression, such as in ovarian cancer 16 and gastric cancer. 17 In NSCLC, miR-598 expression has been found to be significantly low and associated with the malignant progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the expression of mirR-598 has been down-regulated in tissue and cells of gastric cancer, and miR-598 over-expresses can inhibit and promote gastric cancer proliferation and metastasis and apoptosis (23,24). Zeng et al (25) found that miR-598 expression in ovarian cancer cells is downregulated and miR-598 inhibition could reverse the circCELSR1 down-regulation on ovarian cancer cell proliferation and metastasis and promote apoptosis. The findings of this study demonstrated that miR-598 was downregulated with Zeng and Liu-like, stomach cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%